Taurolidine lock solutions for the prevention of catheter-related bloodstream infections: a systematic review and meta-analysis of randomized controlled trials. - Yong Liu; An-Qiang Zhang; Lin Cao; Hong-Tao Xia; Jun-Jie Ma (PLoS ONE, 2013)
Background Catheter-related bloodstream infections (CRBSIs) are a significant cause of morbidity and mortality in critically ill patients, contributing to prolonged hospital stays and increased costs. Whether taurolidine lock solutions (TLS) are beneficial for the prevention of CRBSIs remains controversial. In this meta-analysis, we aim to assess the efficacy of TLS for preventing CRBSIs. Methods We conducted a systematic search of PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials. Eligible studies included randomized controlled trials that reported on the effects of TLS for preventing CRBSIs. The primary outcome in these studies was catheter-related bloodstream infections, with microbial distribution of CRBSI and catheter-associated thrombosis as secondary outcomes. Data were combined using random-effects models owing to significant clinical heterogeneity. Results Six randomized controlled trials (RCTs) conducted from 2004 through 2013 involving 431 patients and 86,078 catheter-days were included in the review. TLS were significantly associated with a lower incidence of CRBSIs when compared to heparin lock solutions (Risk Ratio [RR], 0.34; 95% Confidence Interval [CI], 0.21-0.55). Use of TLS significantly decreased the incidence of CRBSIs from gram-negative (G-) bacteria (P = 0.004; RR, 0.27; CI, 0.11-0.65), and was associated with a non-significant decrease in gram-positive (G+) bacterial infections (P = 0.07; RR, 0.41; CI, 0.15-1.09). No significant association was observed with TLS and catheter-associated thrombosis (RR, 1.99; CI, 0.75-5.28). Conclusions The use of TLS reduced the incidence of CRBSIs without obvious adverse effects or bacterial resistance. However, the susceptibility of G+ and G- bacteria to taurolidine and the risk for catheter-associated thrombosis of TLS are indeterminate due to limited data. The results should be treated with caution due to the limited sample sizes and methodological deficiencies of included studies. Therefore, additional well-designed and adequately powered RCTs are needed to confirm these findings.